Tantangan Industri Kreatif-Game Online di Indonesia - Choirul Fajri (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
Information and communication technology currently has grown to such an extent, not only to meet the needs for information only, but now has grown to the fulfillment of the will of entertainment. These developments, and then bring up the creative industries technology-based communication and information, one of them is online gaming. Creative industries in this area, has become a phenomenon by itself, and makes it as one of the important sectors for economic growth. However, based on the data we get, there are still constraints faced in the development of this industry, such as: the limitations of knowledge, capital, the absence of Government support, as well as the lack of adequate infrastructure. The negative impact was unavoidable as well as from the industry, for example, will the existence of addiction for the gamers who have an impact on crime and action elements of pornography are also inherent in this online game. Therefore, it takes the good cooperation between the developers of the game and also the Government to be able to develop the online gaming industry. There is awareness of the game developer to make a quality game play and has educational values.